2007
DOI: 10.1097/ico.0b013e3180de1e04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Corneal Topographic Characteristics of Keratoconus With Orbscan II in Patients With and Without Atopy

Abstract: : This study shows that corneal topographic and pachymetric characteristics of keratoconus may be different in atopic eyes from those in nonatopic eyes. Atopic keratoconus patients could possibly be evaluated as a separate entity in keratoconus disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 22 publications
2
43
2
2
Order By: Relevance
“…86,87 Several authors did not find a statistically significant difference between a group of control and keratoconic patients. 31,88 Yet, Kaya et al 85 showed that individuals with keratoconus and atopy had a steeper and thinner ectatic area than individuals with keratoconus but without atopy. However, it is possible that the itching induced by atopy, which leads to eye rubbing is the most significant contributor to KC.…”
Section: Atopymentioning
confidence: 99%
See 1 more Smart Citation
“…86,87 Several authors did not find a statistically significant difference between a group of control and keratoconic patients. 31,88 Yet, Kaya et al 85 showed that individuals with keratoconus and atopy had a steeper and thinner ectatic area than individuals with keratoconus but without atopy. However, it is possible that the itching induced by atopy, which leads to eye rubbing is the most significant contributor to KC.…”
Section: Atopymentioning
confidence: 99%
“…3,12,18,79,84,85 However, the effect of atopy is controversial. 86,87 Several authors did not find a statistically significant difference between a group of control and keratoconic patients.…”
Section: Atopymentioning
confidence: 99%
“…16 Several reports have identified topographic parameters important in distinguishing keratoconic from normal corneal morphologic features; these include asymmetric bow-tie astigmatism, posterior corneal elevation, local areas of increased surface power, central corneal keratometric steepening, and inferior-superior dioptric asymmetry. 3,15,17 Keratoconus is largely regarded as a bilateral but asymmetric disease, affecting 1 eye earlier and more severely in most cases. Reports of inter-eye asymmetry between the corneal curvatures of keratoconus have noted differences of 3.50 to 4.00 diopters (D), 18,19 although the causes of this asymmetry have yet to be established.…”
mentioning
confidence: 99%
“…They affect several epithelia including the skin (atopic dermatitis, AD), the respiratory tract (asthma, allergic rhinitis) and the eye (allergic conjunctivitis). Atopic diseases, especially AD, have been associated with KC in a number of uncontrolled studies with conflicting data according to the type of patient recruitment [2,3,4,5,6,7] (table 1). …”
Section: Introductionmentioning
confidence: 99%